Management of Sports and Recreation Centers in Karanganyar District Through Knowledge Based Worker-Based Sports Human Resources Development - Zandra Dwanita Widodo; Achmad Choerudin; Atik Lusia; Dwinanda Ripta Ramadhan; Nabila Afrannida Kultsum (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to explore innovation in management through the development of knowledge-based sports human resources in the sports and recreation center of Karanganyar Regency. The main focus of this study is on the development of knowledge-based sports human resources (knowledge-based workers). In the corporate context, the development of sports human resources should involve several important aspects, including participation in training, mandatory learning, training to improve skills relevant to various modern positions, as well as providing a broad career path and competency development. In addition, performance and competency assessment as well as effective communication in providing feedback are also an integral part of this process. Knowledge-based development is considered a fundamental requirement for achieving sustainable competitive advantage. This underlines the important role of professional intellect in creating value and profits for sports and recreation centers to face business competition. The concept of professional intellect is implemented at four levels, namely cognitive knowledge (professional intellect), skill improvement (advanced skills), system understanding (system understanding), and self-motivated creativity (self-motivated creativity)